The Road to Mastery: Strategies and Challenges in Moving from B2 to C1/C2 Levels (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Reaching advanced proficiency (C1 or C2) in a foreign language represents a substantial leap from the upper-intermediate (B2) level, demanding mastery of nuanced vocabulary, complex grammatical structures, and the ability to communicate fluently in diverse contexts. While many learners achieve B2 competence, progression often stagnates due to functional comfort, limited advanced input, and ineffective strategies. This study uses a mixed-methods approach - combining literature review, interviews with expert educators, and learner activity logs to identify efficient strategies for rapid advancement. Findings indicate that immersion, deliberate vocabulary learning, structured speaking and writing, and sustained engagement with authentic materials accelerate progress. Learners dedicating 15-20 hours weekly can reach C1 in 6-12 months, while C2 typically requires 12-18 months. The study provides evidence-based guidance for autonomous learners and curriculum designers.